2015
DOI: 10.2308/accr-51032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Auditor Rotation, Professional Skepticism, and Interactions with Managers on Audit Quality

Abstract: We examine whether the effect of mandatory auditor rotation on audit quality depends on the mental frame auditors adopt in evaluating management representations. In practice, auditors can alternately frame their assessments of management representations in terms of their potential dishonesty (what we term skepticism) or potential honesty. Using psychology theory and a laboratory experiment, we predict and find that mandatory rotation improves audit quality when an auditor takes an honesty frame, but that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 69 publications
2
38
0
5
Order By: Relevance
“…In turn, auditors maximize expected payoffs by removing all red marbles supported by the available evidence. While prior studies sometimes operationalize audit‐like games with mixed‐strategy equilibria (e.g., Bowlin, Hales, and Kachelmeier [], Bowlin, Hobson, and Piercey []), the pure‐strategy equilibrium in our setting affords the benefit of simplicity, while preserving the key tensions faced by auditors and reporters. DeAngelo [] defines audit quality as the joint probability that auditors (1) detect misstatements and (2) respond appropriately.…”
Section: Methods and Designmentioning
confidence: 99%
“…In turn, auditors maximize expected payoffs by removing all red marbles supported by the available evidence. While prior studies sometimes operationalize audit‐like games with mixed‐strategy equilibria (e.g., Bowlin, Hales, and Kachelmeier [], Bowlin, Hobson, and Piercey []), the pure‐strategy equilibrium in our setting affords the benefit of simplicity, while preserving the key tensions faced by auditors and reporters. DeAngelo [] defines audit quality as the joint probability that auditors (1) detect misstatements and (2) respond appropriately.…”
Section: Methods and Designmentioning
confidence: 99%
“…Although experiments might be an effective tool for investigating the effects induced by mandatory audit‐firm versus audit‐partner rotation, little experimental research has thus far focused on the impact of the rotation system. Some experimental studies have investigated the impact of audit‐firm rotation on factual independence or factual audit quality, mostly finding a positive impact (e.g., Arel, Brody, & Pany, ; Bowlin, Hobson, & Piercey, ; Dopuch, King, & Schwartz, ; Hatfield, Jackson, & Vandervelde, ; Kemp, Reckers, & Arrington, ; Wang & Tuttle, ). Gates, Lowe, and Reckers (), from an experiment with MBA and law students at a top‐ranked metropolitan university in the USA, reported that audit‐firm rotation increases confidence in reported earnings.…”
Section: Theoretical Background Prior Research and Development Of Tmentioning
confidence: 99%
“…In an experimental setting, auditors new to a client propose larger audit adjustments than continuing auditors (Hatfield et al, 2011) and they decrease audit effort and increase partner time spent on documentation at the expense of other quality-enhancing activities ahead of a partner rotation (Winn, 2014). Another experiment finds that mandatory rotation impedes audit quality when an auditor takes on a sceptical frame (Bowlin et al, 2015).…”
Section: The Effect Of An Anticipated Partner Rotation On the Need Fomentioning
confidence: 99%
“…Prior research has examined the link between audit regulations, such as inspections and partner rotation, and auditor behaviour (Carey and Simnett, 2006;Gramling et al, 2011;Shefchik, 2014;Winn, 2014;Bowlin et al, 2015). To expand our understanding of how regulation may influence the audit process, we use an experiment to measure the effect of an anticipated inspection of a client's audit file by a regulator or an anticipated partner rotation on the allocation of staff to engagements.…”
Section: Introductionmentioning
confidence: 99%